Pengaruh Penerapan Sistem Pengendalian Manajemen (SPM), Motivasi Dan Gaya Kepemimpinan Terhadap Kinerja Manajerial PT. Bank Pembangunan Daerah Jambi - Wulan Novi Hastuti; Netty Herawaty; Lutfi Lutfi (Universitas Batanghari, 2022)
This study aims to determine and analyze whether the application of management control systems, motivation and leadership style affect managerial performance at PT. Bank Pembangunan Daerah Jambi either simultaneously or partially. The implementation of management control system, motivation and leadership style are independent variables, while managerial performance is the dependent variable. This type of research is quantitative where the type of data used is primary data in the form of a questionnaire at PT. Bank Pembangunan Daerah Jambi. The data analysis technique used in this research is multiple linear regression analysis. The population in this study is all levels of organizational management at PT. Bank Pembangunan Daerah Jambi with a total sample of 52 people. The results of this study indicate that management control system, motivation and leadership style affect managerial performance at PT. Bank Pembangunan Daerah Jambi.